2021
DOI: 10.1002/hbm.25714
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling whole‐brain dynamics in normal aging through Hidden Markov Models

Abstract: During normal aging, the brain undergoes structural and functional changes. Many studies applied static functional connectivity (FC) analysis on resting state functional magnetic resonance imaging (rs‐fMRI) data showing a link between aging and the increase of between‐networks connectivity. However, it has been demonstrated that FC is not static but varies over time. By employing the dynamic data‐driven approach of Hidden Markov Models, this study aims to investigate how aging is related to specific characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…They correspond to commonly observed functional resting-state networks (at the spatial level within the DPC 4 , 6 ) including the DMN, SMN, visual, frontoparietal, attentional, and ANP. The spatial maps primarily showed patterns that are in line with the previous work 32 , 33 , 50 that examined the large-scale UK Biobank data. This provides confidence in the generalizability of the HMM in our study which had a modest sample size.…”
Section: Discussionsupporting
confidence: 85%
“…They correspond to commonly observed functional resting-state networks (at the spatial level within the DPC 4 , 6 ) including the DMN, SMN, visual, frontoparietal, attentional, and ANP. The spatial maps primarily showed patterns that are in line with the previous work 32 , 33 , 50 that examined the large-scale UK Biobank data. This provides confidence in the generalizability of the HMM in our study which had a modest sample size.…”
Section: Discussionsupporting
confidence: 85%
“…The number of states was decided according to the free energy (80). Previous HMM studies had also confirmed that 6-12 states were appropriate for describing brain function temporal dynamics (43,45,(81)(82)(83). Beyond the group-level fractional occupancy, mean lifetime, and transition probability, we calculated each of these three parameters for each participant during each task (see HMM-MAR wiki).…”
Section: Methodsmentioning
confidence: 99%
“…The choice of the model order was performed as in 30 . In brief, after tting the model with the number of states ranging from 2 to 15, different indices were evaluated: the free-energy and the average loglikelihood (avLL), as indices of goodness of the t and the coe cients of variation (CVs) to quantify the precision of the estimates.…”
Section: Hidden Markov Model -Setupmentioning
confidence: 99%
“…A Wilcoxon's rank sum test followed by multiple comparison correction (FDR, α = .05) was applied to test for signi cant differences between states graph metrics. Finally, we applied the Louvain's community detection algorithm 63 on the thresholded FCs matrices, exploiting the framework described in 30 . Once obtained the organisation of RSNs in communities for each state, we computed the Jaccard index to evaluate the similarity between states modular organisation.…”
Section: B Graph-based Analysismentioning
confidence: 99%
See 1 more Smart Citation